2023
DOI: 10.3947/ic.2023.0059
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Rapid Antigen Screening Tests for SARS-CoV-2 Infection at Correctional Facilities in Korea: March - May 2022

Hye Young Lee,
Young-Joon Park,
Mi Yu
et al.

Abstract: Background The number of confirmed cases of individuals with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection increased rapidly due to the Omicron variant. Correctional facilities are vulnerable to infectious diseases, and they introduced rapid antigen tests (RATs) to allow for early detection and rapid response. We aimed to evaluate the diagnostic performance and usefulness of SARS-CoV-2 RATs in newly incarcerated people. Materials and Methods We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
0
0
Order By: Relevance
“…Indeed, we found that patients receiving immunosuppressive therapy were more likely to have a positive PCR result >30 days after COVID-19 onset, presumably as a result of impaired viral clearance. Several studies have suggested that lung cancer [ 19 ] or immunosuppressive therapy [ 20 ] delays the clearance of the virus. We found some cases remained PCR-positive for up to 100 days (Figures 2A - 2B ).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, we found that patients receiving immunosuppressive therapy were more likely to have a positive PCR result >30 days after COVID-19 onset, presumably as a result of impaired viral clearance. Several studies have suggested that lung cancer [ 19 ] or immunosuppressive therapy [ 20 ] delays the clearance of the virus. We found some cases remained PCR-positive for up to 100 days (Figures 2A - 2B ).…”
Section: Discussionmentioning
confidence: 99%